The Determinants of Micro and Small Enterprises Performance: An Empirical Study of Millennial and Centennial Entrepreneurs - Ambinari, Nur Ayu; Kholid, Muamar Nur (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
The purpose of this study is to determine the factors affecting the enterprise performance of Micro and Small Enterprises (MSEs) among generations Y (millennial) and Z (centennial) entrepreneurs during the Covid-19 pressure under the theory of Resource-Based View. Data were collected by online questionnaires to 227 generation Y and Z respondents and were analyzed using the Partial Least Squares Structural Equation Model (PLS-SEM). The data analysis findings indicate that risk-taking and networking positively affect micro and small enterprise performance positively and positively affect entrepreneurial competencies. Entrepreneurial competencies also significantly positively affect micro and small enterprise performance. While technology usage has no significant effect on micro and small enterprise performance, it substantially affects entrepreneurial competencies. Theoretical and practical contributions are provided.